Therapeutic role of exosomes and conditioned medium in keloid and hypertrophic scar and possible mechanisms - Zhong, Yixiu; Zhang, Youfan; Yu, Aijiao; Zhang, Zhiwen; Deng, Zhenjun; Xiong, Kaifen; Wang, Qi; Zhang, Jianglin (Frontiers in Physiology, 2023)
Exosomes, ranging from 40-160 nm in diameter, are extracellular lipid bilayer microvesicles that regulate the body's physiological and pathological processes and are secreted by cells that contain proteins, nucleic acids, amino acids and other metabolites.Previous studies suggested that mesenchymal stem cell (MSC)-derived exosomes could either suppress or support keloid and hypertrophic scar progression. Although previous research has identified the potential value of MSC-exosomes in keloid and hypertrophic scar, a comprehensive analysis of different sources of MSC-exosome in keloid and hypertrophic scar is still lacking. This review mainly discusses different insights regarding the roles of MSC-exosomes in keloid and hypertrophic scar treatment and summarizes possible underlying mechanisms.